Methodological framework for the allocation of work packages in global software development. Issue 5 (21st September 2013) - Ruano‐Mayoral, Marcos; Casado‐Lumbreras, Cristina; Garbarino‐Alberti, Helena; Misra, Sanjay; Biró, Miklós; Messnarz, Richard; Colomo‐Palacios, Ricardo
ABSTRACT Global software development in software development industry is a new aspect for many software project managers. In this scenario, the allocation of work packages among project participants is not a simple task. This allocation was traditionally determined by availability and competence but this new trend introduces complexity in an already complex process. Given the need to define new models to guide managers in these operations, this paper presents a framework to allocate work packages among project participants. Apart from the introduction of the framework itself, the results of its implementation are presented. These results show a notable output of the implementation in terms of accuracy of task execution to planning, effect introduction and overall satisfaction. Copyright © 2013 John Wiley & Sons, Ltd.